A Structured Process for Supervising Students’ Final Theses and Projects in Computer Science - Schefer-Wenzl, Sigrid; Miladinovic, Igor (International Journal of Advanced Corporate Learning (iJAC), 2022)
Bachelor’s and Master’s theses are an opportunity for students to dive deep into a research question and gain in-depth knowledge about a research topic. At the end of a curriculum, theses act as a kind of bridge between the educational stage and work or further study. Thesis supervision is a resource-intensive task and often a critical factor for the quality of a thesis. After decades of experience with different methods, we have developed a concept for continuous thesis supervision and applied it to two specific degree programs at our university, the Bachelor’s program in Computer Science and Digital Communication and the Master’s program in Software Design and Engineering. Compared to traditional supervision methods, this concept has led to a higher adherence to deadlines and to a higher quality of the final theses. In this paper, we present our findings on different types of supervisors and our concept for continuous thesis supervision, which can be adapted to each identified supervisor type. This concept comprises several methods, intended to inspire other supervisors to choose the set of methods that best suits their needs. We also describe how this concept can be adapted for project-based courses.